Analysis of the importance and priority of male and female players in mixed doubles table tennis - Yang, Q.; Li, M. (PLOS ONE, 2026)
To examine the relative importance and tactical priorities of male and female players in mixed doubles table tennis, this study analysed 35 matches involving world top-50 ranked players. A novel Five-Phase and Four-Mode Model was eveloped and applied. Performance was then evaluated using multiple regression and total decision coefficient method. The results indicate that: (1) Compared to conventional methods, the proposed model demonstrates superior alignment with mixed doubles characteristics in three key dimensions: phase segmentation, assessment indicators, and data acquisition protocols. This methodological advancement significantly enhances the characterization of doubles-specific technical and tactical patterns. (2) Male players demonstrated a higher performance impact (1.3 times that of female players), which is consistent with empirically observed "male-dominant, female-supportive" dynamic in mixed doubles. (3) The "lady-first" strategy is confirmed as an effective match arrangement principle: during service round, the female player should serve first; in receiving scenarios, regardless of the server`s identity, the female player should be the primary receiver.